Polyphagous Pests of Crops 2021
DOI: 10.1007/978-981-15-8075-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Fall Armyworm (Spodoptera frugiperda)

Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), originated from America but is reported recently from Africa and the Asia-Pacific. FAW has caused huge international concern since its outbreak in Africa since 2016 and in Asia since mid-2018. The chapter mainly reviews its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…and Trichogrammatoidea sp. (both Hymenoptera: Trichogrammatidae) [66,68,69,73]. The occurrence of T. remus for instance was reported in Benin, Cameroon, Côte d'Ivoire, Kenya, Niger and South Africa.…”
Section: Biological Control Of Faw In Africamentioning
confidence: 99%
“…and Trichogrammatoidea sp. (both Hymenoptera: Trichogrammatidae) [66,68,69,73]. The occurrence of T. remus for instance was reported in Benin, Cameroon, Côte d'Ivoire, Kenya, Niger and South Africa.…”
Section: Biological Control Of Faw In Africamentioning
confidence: 99%
“…The fall armyworm (Spodoptera frugiperda; FAW) is one of the important examples that highlight the need for national, regional, and transcontinental coordination in effectively managing a highly destructive transboundary pest. The global spread of FAW within a very short timeframe has caused huge concern, especially in Africa (Otim et al, 2021;Prasanna et al, 2018) and Asia (Deshmukh et al, 2021), as the pest poses a serious threat to the food and nutrition security and livelihoods of hundreds of millions of farming households. Besides the economic damage, especially in maize, the FAW invasion has resulted in the heavy use of pesticides, increasing the cost of cultivation, while posing a serious threat to natural enemies (parasitoids and predators of FAW), human health, and the environment (Tepa-Yotto et al, 2021).…”
Section: Integrated Management Of Transboundary Crop Pests and Pathogensmentioning
confidence: 99%
“…FAW was officially reported outside the Americas for the first time in West Africa in January 2016 (Goergen et al 2016 ), and by January 2018, the pest was reported in over 40 African countries (Prasanna et al 2018 ). In Asia, FAW was first reported in the southern Indian state of Karnataka in May 2018 (Sharanabasappa et al 2018 ; Shylesha et al 2018 ), and subsequently in all the maize-growing states in the country (Suby et al 2020 ; Deshmukh et al 2021 ). Between 2018 and 2021, the pest rapidly spread across the Asia–Pacific region and has been reported from Yemen, Bangladesh, Myanmar, China, Thailand, Sri Lanka, Nepal, Philippines, Vietnam, Indonesia, Australia, South Korea, Cambodia, Papua New Guinea, Timor Leste, New Caledonia, Jordan, Syria and the United Arab Emirates (reviewed by Prasanna et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%